2015
DOI: 10.1517/14728222.2015.1016424
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis in salivary gland tumors: from clinical significance to treatment

Abstract: The available data suggest that microvessel density (MVD) evaluation may be capable of discriminating between benign and malignant SGTs, while the use of CD105 antibody seems to be the most suitable. Substantial evidence also suggests that MVD and VEGF expression could be used as prognostic factors in malignant SGTs. Although several agents have shown antiangiogenic activities in adenoid cystic carcinoma cells and xenograft tumors, limited effectiveness in the existing clinical trials was noted. Further studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…CD105 represents a suitable angiogenic marker, because it is preferentially associated with recently formed blood vessels . In the current study, we observed that the great majority of stained vessels were small and thin‐walled structures and the expression of this protein was increased in malignancies than in pleomorphic adenoma.…”
Section: Discussionsupporting
confidence: 53%
“…CD105 represents a suitable angiogenic marker, because it is preferentially associated with recently formed blood vessels . In the current study, we observed that the great majority of stained vessels were small and thin‐walled structures and the expression of this protein was increased in malignancies than in pleomorphic adenoma.…”
Section: Discussionsupporting
confidence: 53%
“…The latest, also known as endoglin, is an activated ECs marker, part of the transforming growth factor β receptor complex that plays a key role in tumor-induced angiogenesis [17]. However, the evaluation of tumor angiogenic activity by MVD assessment lies under the constriction that not all microvessels detected necessarily contribute to tumor perfusion [18].…”
Section: Angiogenesis' Evaluationmentioning
confidence: 99%
“…Angiogenesis inhibitor is a critical component in ACC treatment [ 6 , 18 ]. The microvessel density and VEGFR expression were closely related to the worse survival of ACC [ 12 ]. Some studies indicated that when combined with eribulin, antiangiogenic therapy could play a stronger antitumor effect [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy and targeted therapies have proven poor response rate and survival benefit [ 6 , 10 ]. Recent studies suggest that the microtubule inhibitor eribulin [ 11 ] and antiangiogenic therapy [ 12 , 13 ] could control ACC to some extent. Here, we report the first case of advanced perianal ACC with multiple pulmonary metastases that presented a durable response to eribulin and anlotinib after the failure of conventional radiotherapy and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%